Training on Developing Virtual Reality–Based Learning Media for the Indonesian Teachers Association (IGI) Pekanbaru - Akhmad Suyono; Merlina Sari; Fitri Wulandari; Nabila Khairunnisa (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
Digital literacy is important in education in the era of Society 5.0, because teachers are required to be facilitators in supporting students to become digital learners. To support the success of students in becoming digital learners, the role of teachers in the use of technology during learning activities also contributes. The existence of these demands makes the use of virtual reality media in the learning environment an alternative that can be done to create learning activities that meet the demands in the Society 5.0 era. The purpose of this service activity is to improve the digital literacy of IGI Pekanbaru. as well as introduce virtual reality-based learning media as a renewable learning media innovation to support student learning activities in the digital era. In this service, the methods include presentation, demonstration, and practice. The results showed that teacher training in making VR learning media can improve their digital literacy. This training can also help teachers create interactive and interesting technology-based collaborative learning media for modern learning.